An analytical approach for optimal design of heat sinks under forced convection - Miguel, A. F. (2013)
Saving energy is just as important as generating energy. In this paper, we seek an optimized structure that achieves a certain level of heat transfer rate under a minimum pumping power to drive the ﬂuid stream. Constraints are speciﬁed by the ﬂow regime (laminar and turbulent), admissible boundary conditions on the walls (prescribed temperature and constant heat ﬂux), and design standards. The study will help designers with more eﬀective basic tools for the conceptual design of system and in establishing proper operating procedures.